Release and establishment of three species of Phytoseiidae mites for the control of Tetranychidae mites in a cassava crop - MESA, NORA CRISTINA; DUQUE, MYRIAM CRISTINA (Revista Colombiana de Entomología, 1994)
The times Phytoseiidae mites have been successfully introduced and established in field crops to control Tetranychidae mites are relatively scarce, possibly due to methodological reasons or [o specific characteristics of the species involved. Any plan that involves the integrated management of the cassava green mite should establish a methodology of field release as well as monitoring the establishment, the spreading capacity, and the dynamics of several species. This study covers several of these issues and attempts to assess a release system in which phytoseiids were confined in cages before releasing them in the field. The population dynamics of the species released were recorded throughout the entire crop cycle; The permanence of each specie was then related to the climatic conditions and to phytophage populations. A randomized complete block design was used with three replicates; the treatments were the species released (Neoseiulus idaeus, Neoseiulus californicus, Typhlodromalus tenuiscutus, anda check). Each experimental plot consisted of 81 cassava plants; 2000 Phytoseiidae mites of each species were released cm vine plants located in the center of each plot. These plants were then covered with a 3 x 3 x 3 m cage for eight days. Monitoring was carried out on a weekly basis, and the infestation levels on the top, middle, and bottom parts of the plants were recorded. Plants covered with the cage were differentiated from the plants of the rest of the plot. Variables assessed were the phytophage populations using a population scale and the phytoseiid population for each species present in the plot. The system of confinement in cages guaranteed the preadaptation of the phytoseiid populations, and allowed the s ubsequent assessment of establishment (permanence) and spread by recovering the species released. Of the three species released, N. idaeus established throughout the crop and spread to all plots; high phytoseiid percentages were found on all plants. On the other hand, N. californicus andT. tenuiscutusdisappeared from the crop after the first evaluations. One native species, T. manihotae, was found during the experiment, and its populations mixed with those of the species released. Given its characteristics of establishment and spread in cassava crops, N. idaeus is considered a promising candidate for programs to control Mononychellus sp.